Functional regulation of cytotoxic T Cells by gut microbial metabolites - Chang H. Kim (Gut Microbes Reports)
Metabolites from gut microbes have a wide range of functions within the host body. One important function of these metabolites is to either positively or negatively control CD8+ cytotoxic T lymphocytes (CTLs), which can kill cancer and virus-infected cells. In healthy conditions, gut microbes produce a mixture of metabolites that promote CTL activity but also suppress excessive inflammatory responses. However, gut microbial dysbiosis occurs in patients with cancer, and this leads to changes in the production of gut microbial metabolites that can suppress CTL activity, promote inflammatory responses, and/or aid cancer growth. Decreased levels of CTL-promoting metabolites such as short-chain fatty acids, indole metabolites, and polyamines but increased levels of CTL-suppressing metabolites, such as certain bile acids along with oncogenic metabolites, have been observed in patients with cancer. This review summarizes the altered production of major microbial metabolites in patients with cancer and discusses the impact of these changes on anti-cancer CTL responses.